Dosage compensation of X-chromosome inactivation center-linked genes in porcine preimplantation embryos: Non-chromosome-wide initiation of X-chromosome inactivation in blastocysts. (November 2015) - Hwang, Jae Yeon; Oh, Jong-Nam; Park, Chi-Hun; Lee, Dong-Kyung; Lee, Chang-Kyu
Abstract: X-chromosome inactivation (XCI) is an epigenetic mechanism that occurs in the eutherian embryo development to equalize the dosage of X-linked genes between males and females. This event is regulated by various factors, and the genes located in the X-chromosome inactivation center (XIC), which is known to be an evolutionary conserved region, are associated with XCI; however, a number of studies regarding this epigenetic event and genomic region are primarily performed in mouse models despite its species-specific features. Thus, in this study, the porcine XIC was identified, and we analyzed the expression of XIC-linked genes in porcine preimplantation embryos. Comparative sequence analysis revealed that the porcine XIC is synteny with that of human and the non-coding RNAs were less conserved compared with the protein coding genes in the XIC. Among the XIC-linked genes, the expression levels of CHIC1 and RLIM were decreased from morula to blastocyst development and their dosage was compensated between the male and female blastocysts. Additionally, the CpG sites of CHIC1 were approximately 50% methylated in parthenote blastocysts. Contrary to these genes, XIST and LOC102165544, an uncharacterized non-coding gene, showed dramatically increased expression levels after the morula stage and preferential female expression in blastocysts. Imprinted XIST expression was not observed, and their CpG sites were hypo-methylated in parthenogenic blastocysts. These results demonstrate that the porcine XIC consists of an evolutionary conserved structure with fewer sequences conserved non-coding RNAs. In addition, a few XIC-linked genes would likely achieve dosage compensation, but XCI would not be completed in porcine blastocysts. Highlights: Porcine X-chromosome inactivation center is synteny with that of human. Dosages of a few X-linked genes were compensated in porcine blastocysts. Expression of XIST is not imprinted in porcine blastocysts.